PERANAN ORANG TUA DALAM PENGEMBANGAN KOMPETENSI SOCIAL ANAK TUNANETRA - Sidiq, Zulkifli (PEDAGOGIA, 2016)
This study was intended to uncover the challenges faced by parents in developing the social competence of their children with visual impairment who live in the community of sighted children, the results of which are expected to be used as the basis for developing a guidance and counseling program to help them to meet the challenges. The study was carried out using the qualitative approach with the case study strategy; the in-depth interview was used to collect the data, and the Social Attribute Checklist adapted from McClellan Katz (2001) was used to portray the social competence profile of the children. The results of the study indicated that children whose parents were active in exposing them to their social environment and encouraged and supported them to enter a sighted peer group, had a high interest in interacting with their peers, were well accepted by the peer group, and were successful in developing friendship with sighted peers, and, in its turn, these children were also successful in showing a good social competence.